2017
DOI: 10.1111/ecog.02893
|View full text |Cite
|
Sign up to set email alerts
|

Distributional shifts – not geographic isolation – as a probable driver of montane species divergence

Abstract: Understanding the drivers of divergence in historically dynamic systems, such as sky islands, therefore rests on addressing key questions about the genetic consequences of different types of movement. Here we leverage recent conceptual and computational advances to capture variation in movement that can occur among individuals, over time, and across landscapes, under different hypotheses about the processes structuring genetic variation. Specifically, we use an integrative model-based approach (Fig. 1) that em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 66 publications
1
86
0
Order By: Relevance
“…A and S6), suggesting elevation does not currently appear as a major barrier to gene flow for Amphiacusta , although past population connectedness related to shifts in climatic conditions through time due to glacial cycles may have been mediated by elevation (e.g., Massatti and Knowles ; Lanier et al. ; Knowles and Massatti ). Climatic fluctuations across a topographically complex landscape may repeatedly divide and merge populations (McCormack et al.…”
Section: Discussionmentioning
confidence: 99%
“…A and S6), suggesting elevation does not currently appear as a major barrier to gene flow for Amphiacusta , although past population connectedness related to shifts in climatic conditions through time due to glacial cycles may have been mediated by elevation (e.g., Massatti and Knowles ; Lanier et al. ; Knowles and Massatti ). Climatic fluctuations across a topographically complex landscape may repeatedly divide and merge populations (McCormack et al.…”
Section: Discussionmentioning
confidence: 99%
“…To make inferences using x ‐ origin that considers the effects of spatial and temporal environmental heterogeneity on the expansion process, x ‐ origin models the impact of this environmental heterogeneity on the expansion process. Specifically, heterogeneity in habitat suitability might be derived from ecological niche models (ENMs) for the present or the past (Sindato et al., ; Waltari et al., ), or from information on known barriers (e.g., mountain ranges, glaciers and bodies of water; Boehm et al., ; Knowles & Massatti, ; Waltari & Hickerson, ). These suitability maps are used to inform demographic dynamics associated with the expansion process by specifying different likely migration events as a function of spatial and/or temporal environmental heterogeneity.…”
Section: Methodsmentioning
confidence: 99%
“…However, the x ‐ origin pipeline differs in that (i) it infers a novel model parameter of interest Ω (i.e., the actual latitudinal and longitudinal coordinates), and (ii) it utilizes information from spatial summary statistics, specifically, pairwise population measures of F ST and the directionality index, Ψ (Peter & Slatkin, ). As such, x ‐ origin is an approach that focuses on the estimation of a specific parameter of interest—Ω, whereas the iDDC is an approach for model selection among a set of biologically informed demographic hypotheses, the foci of which vary significantly among studies (e.g., Bemmels, Title, Ortego, & Knowles, ; Knowles & Massatti, ; Massatti & Knowles, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, biotic factors can strongly influence local species distributions (Jablonski, ), and some studies have shown macroecological signals of such species interactions (Gotelli, Graves, & Rahbek, ). Further research may integrate biotic factors including species interactions such as competition (Mordecai, Jaramillo, Ashford, Hechinger, & Lafferty, ), specialization (Fjeldså & Lovett, ), population and community dynamics (Locey & Lennon, ; Ralston, DeLuca, Feldman, & King, ), distributional shifts (Knowles & Massatti, ) and niche differentiation (Brown et al, ). A key question is whether and how such factors contribute to the origins and maintenance of species endemism in some areas and not in others that share similar environmental characteristics.…”
Section: Discussionmentioning
confidence: 99%